Konservasi keanekaragaman hayati pada kegiatan pertambangan di kawasan hutan di Indonesia - I Putu Gede Ardhana (Jurnal Ilmu Pertanian Indonesia, 2010)
This paper is carried out in order to study and evaluate the existing of governmental policies and the strategies of Indonesian government for conservation of forest and protective areas and it is also to formulate a sustainable development strategy for forest and protective areas. This study is related with the enactment of the No. 19 Act in 2004 which is implemented in the forest areas, as a new regulation of forestry especially for 13 companies which got the permission in accordance with Presidential Decree No. 41 in 2004 which is a manifestation of synchronization of mining activities in the forest areas. The method of this paper is used a normative legal research to study and evaluate the governmental policies and strategies which deal with mining activities in the forest areas. In this paper I analize a normative vagueness between two Acts, that is No. 11 Act in 1967 as the law of mining and No. 41 Act in 1999 as the law of forestry regarding utilization of forest and conservative forest to overlapping the mining activities. From the result of this study I concluded that in reality the mining is one of the causes of forest destruction. Walhi indicated that the mining locations clearly visible how the face of Indonesian forests are destroyed by excavation, disposal of waste rock and tailing and after mine operation support of the activities and they left about the holes were allowed to continue to open and become toxic acid at the post-mining lake. From the review above for addressing the threat need to formulate a sustainable development strategy for forest and protective areas at least need to revitalize the effort to required legislation concerning forest and conservation of biodiversity for mining activities in the forest areas.